Association of GSTP1 Ile-105-Val Gene Polymorphism with Response to Treatment Among Iraqi Chronic Myeloid Leukaemia Patients - Atyab Abdul Hameed Alaqidi; Maysem Mouayad Alwash (College of Pharmacy / Mustansiriyah University, 2018)
Background: Pharmacogenomics is a relatively new study field that synergize pharmacology with genomics, analyzing the correlation between genetic variation and pharmacokinetics among patients. In the current study, we evaluated the potential effect of functional polymorphisms within gene encoding for Glutathione S transferase pi class (GSTPs) and treatment response among chronic myeloid leukaemia) CML) patients. GSTPs are multifunctional phase II biotransformation enzymes. Their main biologic role is to catalyze the conjugation to endogenous glutathione (GSH). In addition, they can alter drug potency in malignant cells. Polymorphic variants of these enzymes have been implicated in inter-patients' variability in drug response and outcome in CML patients. Aim of study: Evaluating the association between GSTP1 Ile-105-Val gene polymorphism and response to treatment among Iraqi CML patients.  Method: A 'PCR-RFLP' assay was implemented to detect the polymorphic variants of codon 105 GSTP1 gene of forty Iraqi CML patients in chronic phase referring to the National Center of Haematology in the period between November 2017 and July 2018. Results: Our result revealed a statistically significant association between the GSTP1 genotypes and response to treatment. The variant genotypes were associated with inferior log reduction in BCR-ABL1 mRNA and poorer responses comparing to the wild genotype with P-value of 0.006, and 0.034 respectively.